Test report no. PLBO/5: comparative wear tests of PERPRO tools grade N35/RD80 against Sanvik SIP machining EN 9 - College of Aeronautics, (Cranfield) (College of Aeronautics, 1963)
Tools of grade N35/RD80 and S1P were tested at 600 fpm cutting speed, 0.010 in.rev. feed and 0.10 in. depth of cut to 0.030 in. flank-wear. The results showed that the grade S1P gave a tool life between six and seven times greater than grade N35/RD80 together with less crater wear.